A tannin–based agent for coagulation and flocculation of municipal wastewater as a pretreatment for biofilm process. (1st May 2018) - Hameed, Yasir Talib; Idris, Azni; Hussain, Siti Aslina; Abdullah, Norhafizah; Man, Hasfalina Che; Suja, Fatihah
Abstract: The effects of a commercially produced Tannin-based coagulant and flocculant (Tanfloc) in a biofilm process pilot plant treating municipal wastewater were investigated. The investigated flow rates were 10, 14 and 18 L/min for the entire pilot plant, with two additional flows of 22 and 24 L/min were used for flocculation and sedimentation processes only. There was no clear deterioration in flocculation efficiency; even at 24 L/min, where the flocculation time was only 7.5 min. In terms of the clarification process, the enhancement was remarkably good; especially at high flows. Without Tanfloc, the removal efficiencies in the clarifier were less than 20%, 40%, 22% and 8% for turbidity, total suspended solids, biochemical oxygen demand and total phosphate, respectively. Meanwhile, when Tanfloc was used, they achieved 75%, 61%, 60% and 16% for the same respective pollutants. A significant rise in dissolved oxygen level in the aeration tank was observed when Tanfloc was applied (promising saving of energy during aeration). For instance, a dissolved oxygen level of 3 mg/L measured in experiments without Tanfloc, witnessed a climb to 6 mg/L when Tanfloc was used. In addition, volatile suspended solids concentration in the aeration tank decreased when Tanfloc was used (promising less production of sludge). Other measurements of total suspended solids (mg/L), chemical oxygen demand (mg/L) and biochemical oxygen demand (mg/L) in the experiments without Tanfloc were in the range (12–36), (60–104) and (24–50), respectively. Remarkably Tanfloc was able to reduce these measurements to low levels of (9–26), (28–68) and (7–24). In conclusion, the results suggest Tanfloc as promising agent to enhance the performance of clarification in a biological treatment unit. In light of this enhancement, Tanfloc could be used to upgrade existing treatment plants or design compact treatment units. Highlights: No deterioration in flocculation process when HRT was decreased from 20 to 7.5 min. Significant difference in clarifier performance was shown when Tanfloc was used. DO level jumped to almost double the values when Tanfloc was applied.